Generating interspecies connections fostering the human-animal bond in an Animal Shelter in San Jose del Monte, Bulacan - Agosto, Sophia Anne R.
Stray animals are a familiar sight in a developing country like the Philippines. As a way to solve this problem, some of them are rescued and temporarily housed in animal shelters or local pounds to reduce their population. Unfortunately, most of the rescued animals are euthanized primarily due to the low rate of adoption in such facilities. This is the main issue that the design proposal will address, achieved through the study of the human-animal bond. Located in San Jose del Monte City, Bulacan, the animal shelter will essentially focus on creating an environment conducive to the development of a positive human-animal bond. Its spatial programming and design translation will primarily anchor on the mechanisms and theories explaining the interspecies relationship from the perspective of both humans and animals. The application of the Biophilia Hypothesis (Edward Wilson) and Attachment Theory (John Bowlby and Mary Ainsworth) addresses the human aspect of the bond. Meanwhile, Ethology (Karl von Frisch, Konrad Lorenz, and Nicolaas Tinbergen) will be employed to improve the animals’ behavior and compatibility with humans. Finally, animal shelters are know to be resource-intensive facilities; as such, its design will ensure the minimization of resource use through sustainable and tropical architecture.